Comparison of Generation Z and Millennial Communication Styles on Social Media X in the Angry Community - Salsa Guspita; Maylanny Christin (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2025)
The rapid development of social media has shaped the dynamics of social communication, especially among Millennials and Generation Z. This study aims to interpret the communication styles of the two generations on the social media platform X (formerly Twitter), focusing on their interactions in the